Atributos físicos de um Latossolo argiloso sob sistemas de manejo do solo - Pilatti, Maurício Antônio (2018)
Soil management practices imply changes in their physical properties hydropower. The knowledge of the rate of water infiltration in the soil is of fundamental importance to define the soil conservation techniques. This work aims to evaluate the availability of water in Haplortox subjected to different cultures and soil management systems. The experiment was conducted in the experimental area of the Agronomic Institute of Paraná - IAPAR, regional center of Santa Tereza do Oeste, Paraná, Brazil. The experiment consisted of four soil management practices: Traditional Tillage System - SPDT - Scarified Tillage System - SPDE - Gypsum Agricultural Tillage System - SPDG - and Tillage System with Quality - SPDQ. The treatments were distributed in a manner entirely blocks in 12 plots of 20 m x 25 m. The Reclaimers species of soil structure are being deployed in no-tillage system, and consists of three species Reclaimers: Crotalaria juncea (Crotalaria juncea), Crotalaria spectabilis (Crotalaria spectabilis), guandú Bean (Cajanus he) and four species of winter: black Oats (Avena strigosa), Black Oats + forage Turnips (Avena strigosa + Raphanus sativus), black Oats + Lupin Oats (Avena strigosa + Lupinus albus), black Oats + field pea (Avena stringosa + Pisum sativum). Will be collected undisturbed soil samples with volumetric rings for the determination of the following attributes: particle size, soil density, total porosity, macro-and micropores. Laboratory evaluation of the hydraulic conductivity of the saturated soil will be used for the constant Permeâmetro. For the comparison of means of treatments, the Tukey test will be used at 5% of significance, which will be performed through the SISVAR version 5.3 program. For the generation of regression models and graphs, the statistical program R (R CORE TEAM, 2016) will be used. There was a higher correlation between macro and ksat in the soil cover species. In the 0.20 - 0.30 m layer the ksat values were higher due to higher macro volumes. The Ds, macro and ksat presented greater influence on the upper layers in the SPD and scarified SPD. Soya yield was influenced by Ds. The beneficial effects of soil scarification under no-tillage system were not higher than 12 months